A Multi-center Prospective Study for Implementation of an MRI-Only Prostate Treatment Planning Workflow - Greer, Peter; Martin, Jarad; Sidhom, Mark; Hunter, Perry; Pichler, Peter; Choi, Jae Hyuk; Best, Leah; Smart, Joanne; Young, Tony; Jameson, Michael; Afinidad, Tess; Wratten, Chris; et al. (Frontiers in Oncology, 2019)
Purpose: This project investigates the feasibility of implementation of MRI-only prostate planning in a prospective multi-center study. Method and /Materials: A two-phase implementation model was utilized where centers performed retrospective analysis of MRI-only plans for 5 patients followed by prospective MRI-only planning for subsequent patients. Feasibility was assessed if at least 23/25 patients recruited to phase 2 received MRI-only treatment workflow. Whole-pelvic MRI scans (T2 weighted, isotropic 1.6 mm voxel 3D sequence) were converted to pseudo-CT using an established atlas-based method. Dose plans were generated using MRI contoured anatomy with pseudo-CT for dose calculation. A conventional CT scan was acquired subsequent to MRI-only plan approval for quality assurance purposes (QA-CT). 3D Gamma evaluation was performed between pseudo-CT calculated plan dose and recalculation on QA-CT. Criteria was 2%,2 mm criteria with 20% low dose threshold. Gold fiducial marker positions for image guidance were compared between pseudo-CT and QA-CT scan prior to treatment. Results: All twenty-five patients recruited to phase 2 were treated using the MRI-only workflow. Isocenter dose differences between pseudo-CT and QA-CT were -0.04  0.93% (mean SD). 3D Gamma dose comparison pass-rates were 99.7%  0.5% with mean gamma 0.22  0.07. Results were similar for the two centers using two different scanners. All gamma comparisons exceeded the 90% pass-rate tolerance with a minimum gamma pass-rate of 98.0%. In all cases the gold fiducial markers were correctly identified on MRI and the distances of all seeds to centroid were within the tolerance of 1.0 mm of the distances on QA-CT (0.07 0.41 mm), with a root-mean-square difference of 0.42 mm. Conclusion: The results support the hypothesis that an MRI-only prostate workflow can be implemented safely and accurately with appropriate quality assurance methods.